Preparation method and application of catalyst for preparing synthesis gas through methane dry reforming

The supported dry reforming catalyst modified by nano-island oxide solves the problem of inactivation caused by sintering and carbon deposits under high temperature reaction conditions, simplifies the preparation process, improves the activity and stability of the catalyst, and is suitable for large-scale Large-scale industrial application.

CN119281339APending Publication Date: 2025-01-10JIANGNAN UNIV

Patent Information

Application Number
CN202411271754.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing methane dry reforming catalysts are prone to deactivation due to sintering and carbon deposits under high temperature reaction conditions, and the preparation process is complicated, making it difficult to achieve large-scale industrial applications.

Method used

The supported dry reforming catalyst modified with nanoisland oxides is adopted to uniformly disperse sub-nano-sized oxide additives and active metals on the support, and use the defective sites of the oxide additives to enhance the adsorption and activation capabilities of the catalyst to regulate the The electronic structure of active metal avoids carbon decomposition caused by rapid cleavage of methane, and improves the stability of the catalyst through simple preparation methods.

Benefits of technology

The excellent activity, selectivity and stability of the catalyst were achieved. The conversion rate of carbon dioxide to methane reached 96% in high-temperature dry reforming reaction of 800°C, the hydrogen-carbon ratio reached 0.96, and the activity and selectivity were not available in the 2000-hour long-term reaction. There have been obvious changes and are suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281339A_ABST
    Figure CN119281339A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a catalyst for preparing synthesis gas through methane dry reforming, and belongs to the technical field of preparation and application of a catalyst for methane dry reforming. The catalyst is composed of carriers (SiO2, Al2O3, MgO and the like), active metals (Ni, Co and the like), oxide assistants (CeO2, La2O3, ZrO2, MgO, CaO and the like) and alkali metal assistants (Na, K and the like). The oxide auxiliary agent is uniformly dispersed on the surface of the carrier in a nano island structure; the active metal component falls on the surface of the carrier modified by the oxide nano island in a nano particle form. The preparation method of the catalyst is simple, high conversion rates of methane and carbon dioxide, high hydrogen-carbon ratio (H2 / CO) and good catalytic stability can be achieved, in a 2000-hour long-period dry reforming reaction at 800 DEG C, the conversion rates of the carbon dioxide and the methane are up to about 96% and 92%, the hydrogen-carbon ratio is about 0.96, and obvious inactivation does not occur.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a catalyst for preparing synthesis gas through dry reforming of methane, belonging to the technical field of preparation and application of methane dry reforming catalysts. Background Art

[0002] Methane and carbon dioxide are two major greenhouse gases. Their co-conversion and utilization to obtain valuable chemicals is not only conducive to mitigating climate warming, but also conducive to the efficient utilization of carbon resources and the creation of economic value. Methane dry reforming reaction (CH4+CO2=2CO+2H2) is an important way to achieve the co-conversion of methane and carbon dioxide in industry. The product synthesis gas (CO+H2) can be used to obtain a variety of high value-added chemical products such as olefins, aromatics, alcohols, clean fuels, etc. through subsequent Fischer-Tropsch synthesis, methanol synthesis and other pathways.

[0003] Methane dry reforming catalysts can be divided into two categories: precious metal catalysts and non-precious metal catalysts. Among them, although precious metal catalysts (Rh, Ru, Pt, etc.) have higher catalytic activity, stability and resistance to carbon deposition, they are difficult to achieve large-scale industrial application due to their scarce resources and very high prices. Non-precious metal catalysts include Ni, Co, Cu and other catalysts, which are prone to produce carbon deposition under dry reforming reaction conditions and gradually become deactivated.

[0004] Among non-precious metal catalysts, nickel-based catalysts have received extensive attention due to their high catalytic activity. Existing research results show that small-sized nickel nanoparticles have higher catalytic reaction activity and stronger resistance to carbon deposition. However, due to their higher surface energy, small-sized nickel nanoparticles are more likely to sinter, resulting in a significant decrease in the number of exposed active sites and rapid deactivation of the reaction. To this end, existing studies have mostly used the construction of confined structure catalysts to inhibit the sintering of nickel nanoparticles and improve catalytic stability. For example, Chinese invention patent CN104841442A discloses a method for synthesizing a mesoporous confined nickel-based catalyst, which uses a method of vacuum gasification of nickelocene to load nickel species into the pores of a mesoporous carrier, and uses the carrier pore confinement to inhibit the sintering of nickel nanoparticles. Chinese invention patent CN116786153A discloses a method for synthesizing a molecular sieve encapsulated nickel-based catalyst, which achieves high dispersion of nickel nanoparticles, inhibits their sintering, and thus improves catalyst activity and stability. Chinese patent CN118491525A discloses a method for preparing a carbon nanotube-confined nickel catalyst, which uses sugar as a carbon source, mixes it with a nickel source, and obtains a carbon nanotube-confined nickel catalyst by high-temperature pyrolysis and hydrochloric acid treatment. The catalyst did not show obvious deactivation at 800°C and within 70 hours. It is worth noting that the above-mentioned catalyst preparation method is usually more complicated, involves more steps in the synthesis process, and is accompanied by a large amount of waste gas emissions, which is not conducive to large-scale industrial application. In contrast, although large-sized nickel particles have better thermal stability and slow sintering speed, the carbon deposition rate on the catalyst surface is faster, and it is easy to be deactivated due to carbon deposition. Therefore, the development of a simple synthesis method, anti-carbon deposition, efficient and stable methane dry reforming catalyst is an important prerequisite for its large-scale industrial application. Summary of the invention

[0005] [Technical issues]

[0006] The currently reported methane dry reforming catalysts are easily deactivated due to sintering and carbon deposition under high-temperature reaction conditions, and the catalyst preparation process is complicated, making it difficult to achieve large-scale industrial application.

[0007] [Technical solution]

[0008] The present invention provides a simple, practical and effective preparation and application of a methane dry reforming catalyst modified with nano-island oxides, which is characterized by comprising the following steps:

[0009] (1) dispersing the salt precursors corresponding to the carrier and the nano-island oxide additive in water to form a uniform dispersion; then adding a certain amount of alkaline pH regulator to adjust the pH value of the dispersion to 7.5-12 to obtain a mixed system;

[0010] (2) performing solid-liquid separation on the mixed system, collecting the solid, washing it with water, and drying it;

[0011] (3) calcining at 400-800° C. for 2-24 hours to obtain a catalyst carrier modified with nano-island oxides;

[0012] (4) The active metal and the alkali metal promoter are loaded onto the catalyst carrier obtained in step (3) by an impregnation method or a combustion method to obtain a dry reforming reaction catalyst.

[0013] In one embodiment of the present invention, the dispersing process in step (1) specifically includes: adding the carrier into water at room temperature, ultrasonicating or stirring for 0.1-10 hours, adding the salt precursor corresponding to the nano-island oxide additive, and continuing stirring for 0.1-10 hours.

[0014] In one embodiment of the present invention, the carrier includes one or more of silicon dioxide, aluminum oxide, and magnesium oxide; the mass ratio of the carrier to water is 1:(10-1000).

[0015] In one embodiment of the present invention, the salt precursor corresponding to the nano-island oxide additive includes one or more of cerium salt, lanthanum salt, zirconium salt, and calcium salt, and the type of salt includes one or more of nitrate, hydrochloride, sulfate, and acetate.

[0016] In one embodiment of the present invention, the alkaline pH adjuster is aqueous ammonia, urea or ammonium carbonate.

[0017] In one embodiment of the present invention, the active metal includes one or both of nickel and cobalt.

[0018] In one embodiment of the present invention, the alkali metal includes one or both of sodium and potassium.

[0019] In one embodiment of the present invention, the impregnation method generally comprises the following steps: dissolving the precursor salt of the active metal and the precursor salt of the alkali metal additive in an appropriate amount of solvent, and immersing the catalyst support prepared in step (3) in the resulting solution to fully wet the support. The catalyst is then dried, ground, and calcined to obtain a methane dry reforming catalyst.

[0020] Wherein, the solvent is one or more of water, ethanol and glycine solution.

[0021] In one embodiment of the present invention, the combustion method generally comprises the following steps: dissolving the precursor salt of the active metal, the precursor salt of the alkali metal promoter, and the combustion agent in an appropriate amount of solvent, immersing the catalyst support prepared in step (3) in the resulting solution to fully wet the support, and then drying, grinding, burning, and calcining to obtain a methane dry reforming catalyst.

[0022] Wherein, the combustion agent is one or more of glycine, ammonium nitrate and citric acid.

[0023] In one embodiment of the present invention, the precursor salt of the active metal includes one or more of nickel salt and cobalt salt, and the type of salt includes one or more of nitrate, hydrochloride, sulfate and acetate.

[0024] In one embodiment of the present invention, the precursor salt of the alkali metal auxiliary agent includes one or more of sodium salt and potassium salt, and the type of salt includes one or more of nitrate, hydrochloride, sulfate and carbonate.

[0025] In one embodiment of the present invention, the mass fraction of active metal in the catalyst is between 0-30wt% and is not zero.

[0026] In one embodiment of the present invention, the mass fraction of the nano-island oxide additive in the catalyst is 0-10wt%, preferably 0-10wt%, and not 0.

[0027] In one embodiment of the present invention, the mass fraction of the alkali metal promoter in the catalyst is 0-10 wt%.

[0028] In the preparation process of the present invention, the present invention realizes high dispersion of sub-nanometer-sized oxide additives on the surface of the carrier by an electrostatic adsorption method; and simultaneously adopts an impregnation method or a combustion method to realize the loading of active metals.

[0029] In the preparation process of the present invention, the catalyst constructed based on the carrier modified by oxide nano-islands can effectively enhance the catalyst's ability to adsorb and activate carbon dioxide due to the sub-nanometer-sized oxide structure intrinsically containing a large number of defect sites. At the same time, by changing the concentration of sub-nanometer-sized oxides on the surface, the active metal electronic structure can be flexibly regulated, thereby regulating the methane activation rate and avoiding carbon deposition and deactivation of the catalyst due to rapid cracking of methane.

[0030] The present invention provides a methane dry reforming catalyst modified with nano-island oxides based on the above method.

[0031] In one embodiment of the present invention, the methane dry reforming catalyst is composed of a carrier (SiO2, Al2O3, MgO, etc.), an oxide additive (CeO2, La2O3, ZrO2, MgO, CaO, etc.), an active metal (Ni, Co, etc.) and an alkali metal additive (Na, K, etc.); the oxide additive is uniformly dispersed on the carrier surface in a nano-island structure; the active metal component falls on the carrier surface modified by the oxide additive nano-islands in the form of nanoparticles.

[0032] In addition, the present invention also provides an application of the dry reforming catalyst modified by the nano-island oxide.

[0033] Specifically provided is a method for producing synthesis gas by dry reforming of methane, which utilizes the above-mentioned methane dry reforming catalyst to catalyze the dry reforming reaction.

[0034] In one embodiment of the present invention, the conditions of the dry reforming reaction include: CH4 / CO2 in the raw gas = 1 / (0.1-10), the reaction space velocity is 1-1000L / g / h, the reaction temperature is 500-1000°C, and the reaction pressure is 0.1-10MPa.

[0035] In one embodiment of the present invention, the catalyst needs to be pre-treated by hydrogen reduction before the reaction, the reduction temperature is 400-800°C, the space velocity is 1-100L / g / h, and the reduction pressure is 0.1-10MPa.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention uses nano-island oxides to modify traditional supported dry reforming catalysts. On the one hand, the sub-nanometer-sized oxide modifier interacts with the active metal and can flexibly regulate the electronic structure of the active metal, thereby slowing down the carbon deposition caused by the rapid decomposition of methane during the dry reforming reaction. On the other hand, the sub-nanometer-sized oxide modifier has abundant coordination unsaturated defect sites, which is conducive to the adsorption and activation of carbon dioxide, improves the catalyst's carbon removal ability, and then improves the catalyst's anti-carbon deposition ability, inhibiting carbon deposition from covering the active sites.

[0038] (2) The dry reforming catalyst prepared by the method of the present invention has excellent catalytic activity, selectivity and catalytic stability. In the high-temperature dry reforming reaction at 800°C, the conversion rates of carbon dioxide and methane can reach 96% and 92% respectively, and the hydrogen-carbon ratio reaches 0.96. In addition, the activity of the catalyst and the hydrogen-carbon ratio of the synthesis gas product do not show significant changes in the 2000-hour long-cycle reaction.

[0039] (3) The preparation method of the catalyst is very simple and has few steps, which is suitable for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a transmission electron microscopy image of the cerium dioxide nano-island modified spherical silica carrier prepared in Example 1.

[0041] Figure 2 This is a transmission electron microscopy image of the fresh catalyst prepared in Example 1.

[0042] Figure 3 This is a transmission electron microscopy image of the fresh catalyst prepared in Example 1.

[0043] Figure 4 The X-ray diffraction patterns of the catalysts prepared in Examples 1-3 and Comparative Example 1 after reduction.

[0044] Figure 5 This is a transmission electron microscopy image of the catalyst prepared in Example 1 after 50 hours of reaction.

[0045] Figure 6 This is a transmission electron microscope image of the catalyst prepared in Comparative Example 1 after 50 hours of reaction.

[0046] Figure 7 The catalyst prepared in Example 1 was evaluated for a long-term reaction at 800°C and 9 L / g / h for 2000 h. DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. The protection scope of the present invention is not limited by the following embodiments.

[0048] The evaluation process of the catalyst used in the present invention is as follows:

[0049] The catalyst is evaluated in a fixed bed reactor. Hydrogen reduction pretreatment is required before the catalyst evaluation. The specific process is as follows: 0.2g of catalyst (40-60 mesh) is loaded into a fixed bed reactor, hydrogen is introduced into the reactor, and the temperature is raised to 400-800°C under a hydrogen atmosphere, and maintained for 0.1-10h. After the catalyst reduction is completed, the gas in the reactor is switched to argon, and the reactor is heated to the reaction temperature (500-1000°C) under an argon atmosphere. Subsequently, the gas is switched to a reaction gas of CH4 / CO2=1 / (0.1-10), the pressure is adjusted to 0.1-10MPa, and the gas space velocity is 1-1000L / g / h, and then the methane dry reforming reaction is started.

[0050] Carbon dioxide conversion rate (X CO2 ), methane conversion rate (X CH4 ) and the hydrogen-to-carbon ratio (H2 / CO) are calculated using the following formula:

[0051]

[0052] Where F(i) in 、F(i) out Respectively represent the molar flow rate (mol / min) of gas i (i=CH4, CO2, H2, CO) at the reactor inlet and outlet.

[0053] Example 1

[0054] The catalyst was prepared by the following steps:

[0055] (1) 86 mL of deionized water, 460 mL of ethanol and 11.28 g of 25 wt% ammonia water were mixed and stirred for 15 min. Then 16 g of tetraethyl orthosilicate (TEOS) was slowly dripped into the above solution and the stirring was continued for 6 h.

[0056] (2) The solid obtained in step (1) was centrifuged and washed with water and ethanol three times each.

[0057] (3) Dry the solid obtained in step (2) at 80° C. for 12 h to obtain a spherical SiO2 carrier.

[0058] (4) 1.8 g of the carrier obtained in step (3) was added to 500 mL of deionized water and subjected to ultrasonic treatment to fully disperse the carrier. Then, 0.588 g of Ce(NO3)3·6H2O was added under stirring and the stirring was continued for 30 min.

[0059] (5) Add 1 mL of 2 mol / L ammonia water and continue stirring for 3 min.

[0060] (6) The solid obtained in step (5) was centrifuged and washed with water and ethanol three times each.

[0061] (7) The solid obtained in step (6) was dried at 100°C for 12 hours and then calcined at 600°C for 12 hours to obtain a spherical SiO2 carrier modified with nano-island CeO2 (transmission electron microscopy image as shown in FIG. Figure 1 shown).

[0062] (8) 0.52 g of Ni(NO3)3·6H2O was dissolved in 1.21 g of deionized water, and 2 g of the support obtained in step (7) was added and stirred for 1 h. The mixture was then dried at 80°C for 12 h and calcined at 500°C for 4 h to obtain a CeO2 nano-island modified nickel catalyst.

[0063] The obtained catalyst is molded under a pressure of 40 MPa, and then crushed and sieved to obtain catalyst particles with a size of 40-60 mesh.

[0064] Transmission electron microscopy images of fresh catalysts are shown in Figure 2. Figure 2 and Figure 3 As shown, it can be seen that the catalyst carrier is a relatively regular nano-SiO2 ball with a diameter of about 270nm. The catalyst carrier is evenly covered with island-shaped CeO2 nanoparticles, and the CeO2 particle size is about 1.5nm. Nickel nanoparticles are loaded on the surface of SiO2 modified by nano-island CeO2, and the particle size of nickel nanoparticles is about 30nm.

[0065] The catalyst was evaluated in a fixed bed reactor. 0.2 g of the catalyst was loaded into the fixed bed reactor. The reactor was heated to 700°C at a rate of 5°C / min under a hydrogen atmosphere, with a hydrogen space velocity of 10 L / g / min, and maintained for 1 h. After the reduction was completed, the gas was switched to argon, and the reactor was heated to 800°C at a rate of 5°C / min. Subsequently, a mixed gas of CH4 / CO2 / N2=9 / 9 / 2 (molar ratio) was switched to the reactor, with a gas space velocity of 54 L / g / h, and a methane dry reforming reaction was started for a reaction time of 50 h. During the reaction, the reaction results were detected by online gas chromatography, and the catalyst evaluation results are shown in Table 1.

[0066] Example 2

[0067] The amount of cerium nitrate added in step (4) of Example 1 was adjusted to 0.294 g, and the amount of ammonia water added in step (5) was adjusted to 0.5 mL. The remaining steps and operations remained unchanged. The catalyst evaluation results are shown in Table 1.

[0068] Example 3

[0069] The amount of cerium nitrate added in step (4) of Example 1 was adjusted to 0.147 g, and the amount of ammonia water added in step (5) was adjusted to 0.25 mL. The remaining steps and operations remained unchanged. The catalyst evaluation results are shown in Table 1.

[0070] Comparative Example 1

[0071] The spherical SiO2 carrier was prepared by the steps (1-3) in Example 1, and the catalyst was prepared by the impregnation method in step (8) in Example 1. The remaining catalyst evaluation methods were the same as in Example 1, and the catalyst evaluation results are shown in Table 1.

[0072] Comparative Example 2

[0073] The spherical SiO2 carrier was prepared by following steps (1-3) in Example 1.

[0074] 0.52g Ni(NO3)3·6H2O and 0.588g Ce(NO3)3·6H2O were dissolved in 1.21g deionized water, and 2g of the prepared spherical SiO2 carrier was added and stirred for 1h. Then, the mixture was dried at 80°C for 12h and calcined at 500°C for 4h to obtain a catalyst. The rest of the catalyst evaluation method was the same as in Example 1. The catalyst evaluation results are shown in Table 1.

[0075] Comparative Example 3

[0076] The spherical SiO2 carrier was prepared by using step (1-3) in Example 1, 0.588 g of Ce(NO3)3·6H2O was dissolved in 1.21 g of deionized water, 2 g of the prepared spherical SiO2 carrier was added, and stirred for 1 h. Subsequently, it was dried at 80°C for 12 h and calcined at 500°C for 4 h to obtain a CeO2 impregnated modified carrier.

[0077] 0.52g Ni(NO3)3·6H2O was dissolved in 1.21g deionized water, 2g of the prepared CeO2 was added to impregnate the modified carrier, and stirred for 1h. Then, it was dried at 80℃ for 12h and calcined at 500℃ for 4h to obtain a catalyst. The rest of the catalyst evaluation method was the same as in Example 1, and the catalyst evaluation results are shown in Table 1.

[0078] Comparative Example 4

[0079] The spherical SiO2 carrier is prepared by steps (1-3) in Example 1;

[0080] 1.8 g of the spherical SiO2 carrier obtained in step (3) was added to 500 mL of deionized water and subjected to ultrasonic treatment to fully disperse it. Subsequently, 0.588 g of Ce(NO3)3·6H2O and 0.25 g of CTAB were added under stirring and stirred at 75°C for 7 h; the stirred solution was transferred to an evaporating dish, which was placed in an electric blast drying oven at a temperature of 100°C and dried for 8 h. The dried solid was transferred to an agate mortar and ground evenly, then transferred to a crucible and calcined at 600°C for 12 hours to obtain a CeO2 modified carrier.

[0081] 0.52g Ni(NO3)3·6H2O was dissolved in 1.21g deionized water, 2g of the prepared CeO2 was added to impregnate the modified carrier, and stirred for 1h. Then, it was dried at 80℃ for 12h and calcined at 500℃ for 4h to obtain a catalyst. The rest of the catalyst evaluation method was the same as in Example 1, and the catalyst evaluation results are shown in Table 1.

[0082] Table 1 Catalyst performance results of catalysts involved in Examples 1-3 and Comparative Examples 1-4

[0083]

[0084] From the results in the table, it can be seen that the catalysts modified with cerium dioxide nano-islands in Examples 1-3 have higher reaction activity and hydrogen-to-carbon ratio than the unmodified catalyst in Comparative Example 1, indicating that CeO2 nano-island modification is beneficial to improving the activity, selectivity and stability of dry reforming catalysts. Figure 4The X-ray diffraction pattern of the catalyst after reduction shows that the nickel nanoparticles prepared by the traditional impregnation method are all around 30nm. The coverage of the catalyst active sites by the deposited carbon during the high-temperature methane dry reforming reaction is the main reason for the reduction of catalyst activity. Figure 5 and Figure 6 The transmission electron microscopy image of the catalyst after the reaction shows that after the high-temperature methane dry reforming reaction, the catalyst modified with cerium dioxide nano-islands is conducive to inhibiting the coverage of nickel nanoparticles by deposited carbon, so that it maintains a high reaction activity. On the contrary, for unmodified catalysts, nickel nanoparticles are easily covered by amorphous carbon deposits, which causes the catalyst to deactivate faster. In addition, from the results of comparative examples 1-4, it can be seen that the catalytic performance of CeO2-modified catalysts obtained by traditional impregnation methods or adding surfactants during the impregnation process is similar to that of unmodified catalysts.

[0085] Example 4

[0086] The 0.52 g Ni(NO3)2·6H2O in step (8) of Example 1 was replaced by 0.52 g Ni(NO3)2·6H2O and 0.37 g NaNO3, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 2.

[0087] Example 5

[0088] The 0.52 g Ni(NO3)2·6H2O in step (8) of Example 1 was replaced by 0.52 g Ni(NO3)2·6H2O and 0.26 g KNO3. The other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 2.

[0089] Example 6

[0090] In step (4) of Example 1, 0.588 g of Ce(NO3)3·6H2O was replaced by 0.595 g of La(NO3)3·6H2O. The remaining steps and operations remained unchanged. The catalyst evaluation results are shown in Table 2.

[0091] Example 7

[0092] In step (4) of Example 1, 0.588 g of Ce(NO3)3·6H2O was replaced by 0.896 g of Zr(NO3)2·5H2O. The remaining steps and operations remained unchanged. The catalyst evaluation results are shown in Table 2.

[0093] Example 8

[0094] The 0.588 g Ce(NO3)3·6H2O in step (4) of Example 1 was replaced by 1.12 g Ca(NO3)2·4H2O, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 2.

[0095] Example 9

[0096] The 0.588 g Ce(NO3)3·6H2O in step (4) of Example 1 was replaced by 2.03 g Mg(NO3)2·6H2O, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 2.

[0097] Table 2 Catalyst performance results of catalysts involved in Examples 4-9

[0098]

[0099] From the results in the table, it can be seen that the addition of alkali metal additives (Na or K) can further improve the catalyst stability. At the same time, by comparing Examples 6-9 with Comparative Example 1, it can be seen that the use of nano-island oxides such as La2O3 to modify the catalyst is beneficial to improving the activity and stability of the dry reforming reaction.

[0100] Example 10

[0101] The 0.52 g Ni(NO3)2·6H2O in step (8) of Example 1 was replaced by 0.52 g Co(NO3)2·6H2O, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0102] Comparative Example 5

[0103] The 0.52 g Ni(NO3)2·6H2O in Comparative Example 1 was replaced by 0.52 g Co(NO3)2·6H2O, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0104] Embodiment 11

[0105] The spherical SiO2 carrier obtained in step (1-3) of Example 1 was replaced with gas-phase SiO2 as the carrier, and the remaining steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0106] Comparative Example 6

[0107] The spherical SiO2 carrier in Comparative Example 1 was replaced with gas-phase SiO2 as the carrier, and the remaining steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0108] Example 12

[0109] The spherical SiO2 carrier obtained in step (1-3) of Example 1 was replaced with diatomaceous earth as the carrier, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0110] Comparative Example 7

[0111] The spherical SiO2 carrier in Comparative Example 1 was replaced with diatomaceous earth as the carrier, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0112] Embodiment 13

[0113] The spherical SiO2 carrier obtained in step (1-3) of Example 1 was used to replace Al2O3 as the carrier, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0114] Embodiment 14

[0115] The spherical SiO2 carrier obtained in step (1-3) of Example 7 was used to replace Al2O3 as the carrier, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0116] Comparative Example 8

[0117] The spherical SiO2 carrier in Comparative Example 1 was replaced with Al2O3 as the carrier, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0118] Embodiment 15

[0119] The spherical SiO2 carrier obtained in step (1-3) of Example 1 was replaced with MgO as the carrier, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0120] Comparative Example 9

[0121] The spherical SiO2 carrier in Comparative Example 1 was replaced with MgO as the carrier, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Table 3.

[0122] Table 3 Catalyst performance of catalysts involved in Examples 10-15 and Comparative Examples 5-9

[0123]

[0124]

[0125] From the results in the table, it can be seen that the strategy of constructing nano-island cerium oxide in the present invention has a uniform and obvious promoting effect on the cobalt-based dry reforming reaction and the nickel-based catalytic system loaded with Al2O3, MgO, etc.

[0126] Example 16

[0127] The nano-island-shaped cerium oxide-modified SiO2 carrier prepared in step (1-7) of Example 1 was used to prepare the catalyst by combustion method, and the steps are as follows:

[0128] (1) 0.52 g Ni(NO3)3·6H2O, 0.268 g glycine, and 0.143 g NH4NO3 were dissolved in 1.21 g deionized water, added to 2 g nano-cerium oxide-modified support, and stirred for 2 h.

[0129] (2) Drying at 80°C for 2 h under vacuum conditions, followed by drying at 120°C for 12 h.

[0130] (3) Place the dried sample in a muffle furnace, raise the temperature to 300°C at 1°C / min, and maintain for 1 h.

[0131] (4) Continue to raise the temperature to 550°C at a rate of 2°C / min and maintain for 3 h to obtain a catalyst.

[0132] The catalyst was tableted and sieved to obtain 40-60 mesh particles for subsequent evaluation reaction. The evaluation conditions were the same as in Example 1. The evaluation results are shown in Table 4.

[0133] Embodiment 17

[0134] In Example 16, the space velocity for catalyst evaluation was adjusted to 108 L / g / h, and the other steps and operations remained unchanged.

[0135] Table 4 Catalyst performance of catalysts involved in Examples 16-17

[0136]

[0137] From the results in the table, it can be seen that the nano-island-shaped cerium oxide-modified small-sized nickel catalyst constructed by the combustion method has higher catalytic activity and can maintain catalytic stability at a higher reaction space velocity.

[0138] Embodiment 18

[0139] In Example 1, Example 7, and Example 14, the gas space velocity in the catalyst evaluation experiment was changed to 9 L / g / h, the reaction time was extended to 2000 h, and the other steps and operations remained unchanged. The catalyst evaluation results are shown in Figure 7 and Table 5.

[0140] It can be seen that the Ni / CeO2-SiO2 catalyst prepared by a simple impregnation method with nano-island cerium oxide-modified SiO2 as the carrier has better catalytic activity and stability. In the 2000h long-term evaluation, the carbon dioxide conversion rate reached 96%, the methane conversion rate reached 92%, and the hydrogen-to-carbon ratio reached 0.96, without any obvious decrease in activity and selectivity.

[0141] Table 5 Catalyst performance for 2000h

[0142]

[0143] The above implementation of the present invention is only one of the preferred solutions and should not be used to limit the scope of protection of the present invention. The scope of protection should be based on the scope defined in the claims. Any changes or modifications that are made to the main design concept and spirit of the present invention without any substantial meaning, if the technical problems they solve are still consistent with the present invention, should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a methane dry reforming catalyst, characterized in that The steps include: (1) dispersing the salt precursors corresponding to the carrier and the nano-island oxide additive in water to form a uniform dispersion; then adding an alkaline pH regulator to adjust the pH value of the dispersion to 7.5-12 to obtain a mixed system; (2) performing solid-liquid separation on the mixed system, collecting the solid, washing it with water, and drying it; (3) calcining at 400-800° C. to obtain a catalyst carrier modified with nano-island oxides; (4) Using an impregnation method or a combustion method to load the active metal and the alkali metal promoter onto the catalyst carrier obtained in step (3) to obtain a methane dry reforming catalyst.

2. The method according to claim 1, characterized in that: The carrier in step (1) includes one or more of silicon dioxide, aluminum oxide, and magnesium oxide; the mass ratio of the carrier to water is 1: (10-1000); the salt precursor corresponding to the nano-island oxide additive includes one or more of cerium salt, lanthanum salt, zirconium salt, and calcium salt, and the type of salt includes one or more of nitrate, hydrochloride, sulfate, and acetate; the alkaline pH regulator is ammonia water, urea, or ammonium carbonate.

3. The method according to claim 1, characterized in that The active metal in step (4) includes one or both of nickel and cobalt; and the alkali metal additive includes one or both of sodium and potassium.

4. The method according to claim 1, characterized in that: The impregnation method of step (4) comprises the following steps: dissolving the precursor salt of the active metal and the alkali metal additive in an appropriate amount of solvent, immersing the carrier prepared in step (3) in the resulting solution to fully wet the carrier, and then drying, grinding, and calcining to obtain a methane dry reforming catalyst; the solvent is one or more of water, ethanol, and glycine solution.

5. The method according to claim 1, characterized in that The combustion method of step (4) comprises the following steps: dissolving the precursor salt of the active metal and alkali metal additive and the combustion agent in an appropriate amount of solvent, immersing the carrier prepared in step (3) in the resulting solution to fully wet the carrier, and then drying, grinding and burning to obtain a methane dry reforming catalyst; the combustion agent is one or more of glycine, ammonium nitrate and citric acid.

6. The method according to any one of claims 1 to 5, characterized in that: In the finally obtained catalyst, the mass fraction of the active component is between 0-30wt% and not 0; the mass fraction of the nano-island oxide additive is between 0-10wt% and not 0; and the mass fraction of the alkali metal additive is between 0-10wt%.

7. A methane dry reforming catalyst modified with nano-island oxides prepared by the method according to any one of claims 1 to 6.

8. A methane dry reforming catalyst, characterized in that: It is composed of a carrier, an oxide additive, an active metal and an alkali metal additive; the oxide additive is uniformly dispersed on the carrier surface in a nano-island structure; the active metal component falls on the surface of the carrier modified by the oxide additive nano-island in the form of nanoparticles; The carrier is selected from any one or more of the following: SiO2, Al2O3, MgO; the oxide additive is selected from any one or more of the following: CeO2, La2O3, ZrO2, MgO, CaO; the active metal is selected from any one or more of the following: Ni, Co; The alkali metal promoter is selected from any one or more of the following: Na, K, and the mass fraction of the alkali metal promoter in the catalyst is 0-10wt%.

9. A method for preparing synthesis gas by dry reforming of methane, characterized in that: The dry reforming reaction is catalyzed by the methane dry reforming catalyst described in claim 7 or 8.

10. The method according to claim 9, characterized in that The conditions of the dry reforming reaction include: CH4 / CO2 in the raw gas = 1 / (0.1-10), the reaction space velocity is 1-1000L / g / h, the reaction temperature is 500-1000°C, and the reaction pressure is 0.1-10MPa.

Citation Information

Patent Citations

  • Preparation method of anti-carbon deposition mesoporous confinement methane dry reforming catalyst

    CN104841442A

  • Preparation method and application of nickel-based molecular sieve catalyst for methane dry reforming

    CN116786153A

  • Preparation method and application of carbon nanotube confinement nickel nanoparticle catalyst

    CN118491525A

Cited By

  • Nano island confinement catalyst for methane dry reforming and application of nano island confinement catalyst

    CN122424860A

  • Nano-island confined catalyst for methane dry reforming and application thereof

    CN122424860B